Molecular phylogeny, 3D-structural insights, docking and mechanisms of action of plant beta-galactosidases - Md. Anowar, Hossain; Hairul Azman, Roslan; Md. Rezaul, Karim; Yoshinobu, Kimura (Inderscience Enterprises Ltd., 2016)
Beta-galactosidase (BGAL) is an exoglycosidase that catalyses the hydrolysis of terminal β-linked galactose residues. To better understand the molecular characteristics and structural insights of mango BGAL (MiBGAL), we performed the sequence analyses, reconstruction of the evolutionary tree, homology modelling and molecular docking. BGALs are widely distributed enzymes that evolved from a common bacterial ancestor. Plant BGALs (pBGALs) belong to glycosyl hydrolase-35(GH35) family and had close similarities with fungi BGALs. Three conserved motifs and GH35 putative active site with a consensus sequence G-G-P-[LIVM](2)-x(2)-Q-x-E-N-E-[FY] were identified in 67 BGAL sequences. Modelled 3D structure of MiBGAL is composed of a catalytic TIM barrel domain (domain-I) and three other β-domains, II, III & IV. Structural studies identified the residues Glu182 and Glu251 as the proton donor and nucleophile, respectively in pBGALs that could function through retaining mechanism. p-nitrophenyl-β-D-galactopyranoside and 2-[4-(2-hydroxyethyl)piperazin-1-yl]ethanesulfonic acid could be potential substrate and inhibitor, respectively among the docked-ligands for both tomato BGAL4 and MiBGAL.